Pengaturan Hukum Terhadap Penggeseran Hari Libur dan Implikasinya Terhadap Upah Lembur Tenaga Kerja di Indonesia - Yuli, Yuliana; Devi, Murtanti Fajarrani; Restia, Salsabila; Anindya, Salma Elsa; Asmara, Daffi Allegra; Azzahra, Dinda; Harsanti, Khairunnisa Putri (Media Hukum Indonesia (MHI), 2024)
The shifting of holidays has become an important issue in labor regulation in Indonesia. This policy is often carried out to increase productivity or to comply with government policies. However, shifting holidays can impact overtime wages for workers. This journal aims to analyze the legal regulations regarding holiday shifts and their implications for overtime wages in Indonesia. The research method used is normative analysis of regulations related to labor and overtime wages. The results show that the legal regulations regarding holiday shifts in Indonesia are mainly regulated in Law Number 13 of 2003 concerning Manpower. However, the implementation of these regulations has not fully accommodated the interests of workers, especially regarding overtime wages. This is due to inaccuracies in the definition and provisions related to overtime wages in the applicable law. The implications of holiday shifts on overtime wages for workers in Indonesia can be felt in various aspects, such as a reduction in overtime wages or ambiguity in calculating overtime wages due to holiday shifts. Therefore, improvements in legal regulations are needed to provide better protection for workers regarding overtime wages